(untitled) (Perspectiva Pictorum, 2024)
It seeks to present the paintings that serve as basis for the comparative study that deals with illusionist or quadraturist paintings existing in the ceilings of churches in some Portuguese cities in comparison to similar cases carried out in the city of São Paulo, Itu and Mogi das Cruzes, since in national territory there are not many influences or visual references and typological for the Paulista and Paulistana paintings object of this study. As a methodology, the image comparison between the works was adopted, in addition to results obtained in field research previously carried out in a previous study. After analyzing primarily a large number of Portuguese, Paulista and Paulistana works it was possible to identify and select the Portuguese pictorial works in the cities of Santarém, Aveleda, Silves, Alenquer and etc., which will be compared to the Paulista e Paulistana paintings of the churches of São Paulo as the Church of the First Order of São Francisco de Assis, Church of the Venerable Third Order of São Francisco da cidade de São Paulo, Church of the Venerable Third Order of Nossa Senhora do Carmo; in the city of Itu the Church of Nossa Senhora do Carmo and the Church of Candelária de Itu; in the city of Mogi das Cruzes the Church of the First Order of Nossa Senhora do Carmo and the Church of the Third Order of Nossa Senhora do Carmo.